A methodology to evaluate the effects of river sediment withdrawal: The case study of the Amendolea River in southern Italy. Issue 4 (1st October 2020) - Foti, Giandomenico; Barbaro, Giuseppe; Manti, Andrea; Foti, Pietro; Torre, Adriana La; Geria, Paolo Fantino; Puntorieri, Pierfabrizio; Tramontana, Nicola
Abstract : Sediment deposition is an issue affecting many rivers. To oppose it, sediment withdrawals are often used. However, this practice can trigger further problems in river and coastal sections but, on the other hand, periodic removal of deposited sediments can reduce flooding risk. Also, these sediments can be used for beach nourishment. Therefore, before carrying out a sediment withdrawal, it is necessary to analyze the whole basin to evaluate the consequences for the sediment balance. This paper describes a methodology to evaluate the effects of river sediment withdrawals through a case study on the Amendolea River, a torrential river in southern Italy. In particular, the methodology is divided into three main phases. The first phase was developed with GIS software in order to perimeter and to morphometrically characterize the river basin and its hydraulically and sedimentologically homogeneous sub-basins. The second phase was developed using the HEC-HMS software in order to evaluate the hydrological balance of the basin and its sub-basins. The last phase was developed using the HEC-RAS software (through the SIAM model) in order to identify the areas in erosion, in deposition and in equilibrium. Moreover, through this model is possible to identify the sections where sediments can be withdrawn, and to estimate the possible morphological river changes due to withdrawals. In this case study, the sediments will be taken from the sections where the bottom has elevations near or above those of adjacent lands, such as to increase the flooding risk. Sediment withdrawals will be taken without eroding the bottom and at a distance from the river banks that does not unstabilize them. Finally, the methodology described in this paper is based on the joint use of various open source software and can be used in any other river with hydrological regime similar to the Amendolea River.